(untitled) (Global Journal of Human-Social Science, 2020)
Consisting of two main parts this research paper focuses on how contextual variables influence in-class ESL teaching/learning environment which is based upon observations of three ESL lessons at the upper-intermediate level at the English Preparatory School of a private university in Istanbul, Turkey where students were required to complete a gradual three-level achievement program, starting at an appropriated level determined by a pre-enrolment proficiency and placement exams. Two of the instructors were bilinguals with Turkish as their first language and English as their second language. The third instructor was a native speaker of English with no knowledge in Turkish. The study is presented after a general literature review of contextual variables of ESL, and it focuses primarily on the role played by the teacher, the teacher’s linguistic choices as means of instruction and communication, and the presence/absence of Turkish and English as L1 and L2 factors respectively in the classroom context.